2007
DOI: 10.1177/0002716206299149
|View full text |Cite
|
Sign up to set email alerts
|

Political Brands and Consumer Citizens: The Rebranding of Tony Blair

Abstract: It has become commonplace to speak of political parties and brands. This article looks at the rise of the brand and explains how branding has become the cutting edge of commercial marketing. It examines how the brand concept and research techniques are used in politics and focuses in particular on the rebranding of Tony Blair in the run up to the 2005 U.K. general election. More broadly, it argues that branding is the new form of political marketing. If market research, spin, and advertising were the key signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
68
0
9

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(80 citation statements)
references
References 5 publications
0
68
0
9
Order By: Relevance
“…Research has identified political parties and or politicians as brands (Kavanagh, 1995;Kotler and Kotler, 1999;Harris and Lock, 2001;Smith, 2001;White and deChernatony, 2002;Schneider, 2004;Needham, 2005Needham, , 2006Reeves et al, 2006;Scammell, 2007). Impetus for research based on political brand was driven by the changing nature of post-war Western Democracies.…”
Section: Political Parties Brandingmentioning
confidence: 99%
“…Research has identified political parties and or politicians as brands (Kavanagh, 1995;Kotler and Kotler, 1999;Harris and Lock, 2001;Smith, 2001;White and deChernatony, 2002;Schneider, 2004;Needham, 2005Needham, , 2006Reeves et al, 2006;Scammell, 2007). Impetus for research based on political brand was driven by the changing nature of post-war Western Democracies.…”
Section: Political Parties Brandingmentioning
confidence: 99%
“…The increase in valence issues (Thomassen, 2005), voter volatility (Dalton, 2000(Dalton, , 2012 and practices of political marketing strategy among parties (Hopkin and Paolucci, 1999;Kavanagh, 1995;Nielsen, 2012;Scammell, 2007) have all paved the way for analyzing politics through the lens of brands (Smith and French, 2009;Smith and Speed, 2011). Moreover, some scholars argue that traditional grand variables in voting behavior are slowly decreasing in explanatory power as cleavages have weakened following the resolution of many social conflicts (e.g.…”
Section: On the Need For A Political Brand Concept In Voting Behaviormentioning
confidence: 99%
“…Harrop, 1990;Kavanagh, 1995;Scammell, 2007;Schneider, 2004) have argued that ideas from marketing such as the brand concept can be applied when recognizing the particularities of politics. In practice, the focus should be on service marketing rather than product marketing.…”
Section: On the Need For A Political Brand Concept In Voting Behaviormentioning
confidence: 99%
See 1 more Smart Citation
“…À l'aube des années 2010, le sujet paraît plus pertinent que jamais, à l'heure où plusieurs chercheurs parlent de la marchandisation de la sphère politique et de la transformation des citoyens en citoyens consommateurs (Scammell, 2007(Scammell, , 2003; Lees-Marshment, 2004;Newman, 1999). C'est dans ce contexte qu'il paraît pertinent d'examiner plus attentivement la mise en marché des intérêts par les groupes.…”
unclassified